The adsorption study of Royal Blue Tiafix and Black Tiassolan dyes using bone char as adsorbent - Rowander A Moura; Araceli A Seolatto; Maria E de Oliveira Ferreira; Fernanda F Freitas (Adsorption Science & Technology)
In this study, the potential of bone char for Royal Blue Tiafix and Black Tiassolan dyes adsorption from aqueous solutions was evaluated. The adsorbent was characterized physically and chemically by adsorption/desorption of N 2 at 77 K, scanning electron microscopy, X-ray diffraction, and infrared spectroscopy. The equilibrium adsorption results for bone char can be successfully modeled by the Langmuir and Freundlich isotherms. Pseudo-first-order and pseudo-second-order models were used to describe the kinetic data and rate constants were evaluated. Kinetics of each dye was found to follow pseudo-second-order rate kinetic model, with great correlation (higher than 0.99). In order to reduce the number of experiments to achieve better dye removal efficiency, a 2³ full factorial design with three central points and six axial points was applied in the equilibrium experiments. The variables analyzed were agitation, temperature, and pH.